Prehispanic settlement patterns in the upper Mantaro and Tarma drainages, Junín, Peru : - Parsons, Jeffrey R.; Hastings, Charles M.; Matos Mendieta, Ramiro (Memoirs of the Museum of Anthropology, University of Michigan, 2013)
This monograph is based on six months of systematic regional survey in the Wanka Region of Peru's sierra central, carried out in two field seasons in 1975-1976 by the Junin Archaeological Research Project (JASP) under the co-direction of Jeffrey R. Parsons (University of Michigan) and Ramiro Matos Mendieta (Universidad Nacional Mayor de San Marcos).